hsa-let-7c miRNA Regulates Synaptic and Neuronal Function in Human Neurons - McGowan, Heather; Mirabella, Vincent R.; Hamod, Aula; Karakhanyan, Aziz; Mlynaryk, Nicole; Moore, Jennifer C.; Tischfield, Jay A.; Hart, Ronald P.; Pang, Zhiping P. (Frontiers in Synaptic Neuroscience, 2018)
Non-coding RNA, including microRNA (miRNA) serves critical regulatory functions in the developing brain. The let-7 family of miRNAs has been shown to regulate neuronal differentiation, neural subtype specification, and synapse formation in animal models. However, the regulatory role of human let-7c (hsa-let-7c) in human neuronal development has yet to be examined. Let-7c is encoded on chromosome 21 in humans and therefore may be overexpressed in human brains in Trisomy 21 (T21), a complex neurodevelopmental disorder. Here, we employ recent developments in stem cell biology to show that hsa-let-7c mediates important regulatory epigenetic functions that control the development and functional activity of human induced neuronal cells (iNs). We show that overexpression of hsa-let-7c in human iNs derived from induced pluripotent stem (iPS), as well as embryonic stem (ES), cells leads to morphological as well as functional deficits including impaired neuronal morphologic development, synapse formation and synaptic strength, as well as a marked reduction of neuronal excitability. Importantly, we have assessed these findings over three independent genetic backgrounds, showing that some of these effects are subject to influence by background genetic variability with the most robust and reproducible effect being a striking reduction in spontaneous neural firing. Collectively, these results suggest an important function for let-7 family miRNAs in regulation of human neuronal development and raise implications for understanding the complex molecular etiology of neurodevelopmental disorders, such as T21, where let-7c gene dosage is increased.